Analisis Pemeliharaan Sumber Daya Manusia Kesehatan (SDMK) di PT Tirta Medical Indonesia - Deviyanti, Dira; Zebua, Cynthianoor Fitriana Puteri; Ardhila, Diva; Salsabila, Lutfiyah Nada; Safitri, Safitri; Yuriska, Yuriska; Gurning, Fitriani Paramita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Human resource maintenance is very important for every company, because it not only helps to retain human resources, but also can increase dedication, discipline, and employee loyalty. Human resource maintenance will protect workers from workplace accidents and maintain communication to remain harmonious among human resources. This research uses a qualitative method and deductive approach, where the informants explain the principles of learning content and its application in specific situations. The purpose of this study is to determine the procedures for implementing human resource management maintenance at PT Tirta Medical Indonesia. From the results of the study, it can be seen that PT Tirta Medical Indonesia has implemented good work maintenance methods in accordance with the theory of Drs. H. Melayu S. P Hasibuan, namely effective communication between the company and employees, fair incentives, attention to employee welfare, health, occupational safety, and Pancasila industrial relations. The author recommends that PT Tirta Medical Indonesia continue to maintain and improve human resource maintenance for better employee loyalty and performance.